Candida albicans Antifungal Resistance and Tolerance in Bloodstream Infections: The Triad Yeast-Host-Antifungal - Costa-de-Oliveira, Sofia (Microorganisms, 2020)
Candida albicans represents the most frequent isolated yeast from bloodstream infections. Despite the remarkable progress in diagnostic and therapeutic approaches, these infections continue to be a critical challenge in intensive care units worldwide. The economic cost of bloodstream fungal infections and its associated mortality, especially in debilitated patients, remains unacceptably high. Candida albicans is a highly adaptable microorganism, being able to develop resistance following prolonged exposure to antifungals. Formation of biofilms, which diminish the accessibility of the antifungal, selection of spontaneous mutations that increase expression or decreased susceptibility of the target, altered chromosome abnormalities, overexpression of multidrug efflux pumps and the ability to escape host immune defenses are some of the factors that can contribute to antifungal tolerance and resistance. The knowledge of the antifungal resistance mechanisms can allow the design of alternative therapeutically options in order to modulate or revert the resistance. We have focused this review on the main factors that are involved in antifungal resistance and tolerance in patients with C. albicans bloodstream infections.